2016
DOI: 10.1007/s12154-016-0160-x
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal and anthelmintic activity of novel benzofuran derivatives containing thiazolo benzimidazole nucleus: an in vitro evaluation

Abstract: A novel series of thiazolo[3,2-a]benzimidazole derivatives containing benzofuran nucleus (5a-l) have been synthesized. The key intermediate, substituted benzimidazolsulfanyl benzofuran ethanone (3a-d) was prepared by refluxing the mixture of substituted 2-acetyl benzofuran and substituted 2-mercaptobenzimidazole in acetic acid. The cyclisation of compounds (3a-d) using polyphosphoric acid furnished the corresponding 6-substituted benzofuran thiazolo[3,2-a]benzimidazoles (4a-d). Further, the cyclized compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 39 publications
0
23
0
1
Order By: Relevance
“…It is reported that benzimidazole derivatives were active against Staphylococcus aureus, Escherichia coli, and Candida albicans [1]. Anthelmintic activities of few synthesized benzimidazole derivatives were also reported [2]. Further, in-vitro antiprotozoal activity of synthesized N-azopridinium salts and several betaines were reported adding to the existing pool of biological effects.…”
Section: Introductionmentioning
confidence: 95%
“…It is reported that benzimidazole derivatives were active against Staphylococcus aureus, Escherichia coli, and Candida albicans [1]. Anthelmintic activities of few synthesized benzimidazole derivatives were also reported [2]. Further, in-vitro antiprotozoal activity of synthesized N-azopridinium salts and several betaines were reported adding to the existing pool of biological effects.…”
Section: Introductionmentioning
confidence: 95%
“…[22] Benzofurans are also a part of the molecular structure of a large number of natural products. [23] In recent time, benzofuran derivatives have valuable biological and pharmacological activities including enzyme inhibition, [24] antitubercular, antibacterial, [25] anticonvulsant, [26] anti-Alzheimer, [27] antimicrobial, anti-inflammatory, antioxidant, [28] antiprotozoal, [29] antihyperlipidemic, [30] anticancer, [31] anti-HIV, [32] antihypertensive, [33] analgesic, [34] antiparasitic, [35] antiplasmodial, [36] and antidiabetic. [37] Nanocrystalline metal oxides find excellent applications in the field of synthetic organic chemistry owing to their high catalytic activity, reusable nature, and benign character in the perspective of green chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Benzofurans are also a part of the molecular structure of a large number of natural products . In recent time, benzofuran derivatives have valuable biological and pharmacological activities including enzyme inhibition, antitubercular, antibacterial, anticonvulsant, anti‐Alzheimer, antimicrobial, anti‐inflammatory, antioxidant, antiprotozoal, antihyperlipidemic, anticancer, anti‐HIV, antihypertensive, analgesic, antiparasitic, antiplasmodial, and antidiabetic …”
Section: Introductionmentioning
confidence: 99%
“…The imidazole ring is found in very significant endogenous biomolecules, such as biotin, the autacoid histamine and the essential amino acid histidine [5]. Additionally, the imidazole derivatives are highly important in medicinal chemistry research; a lot of imidazole-containing compounds show biological activities such as antifungal, antibacterial, anti-inflammatory and anthelmintic [6], antitubercular [7], antiblood pressures, antiallergic, antiasthma [8] and anticancer [9]. Antipyrine is well known for its pharmaceutical as well as medical applications including antibacterial, antifungal [10], antituberculosis, anticancer [11], antitumor and antioxidant [12].…”
Section: Introductionmentioning
confidence: 99%